Unique challenges facing Linked Data implementation for National Educational Television. (2nd July 2020) - Pierce, Chris
Implementing Linked Data involves a costly process of converting metadata into an exchange format substantially different from traditional library "records-based" exchange. To achieve full implementation, it is necessary to navigate a complex process of data modelling, crosswalking, and publishing. This paper documents the transition of a data set of National Educational Television (NET) collection records to a "data-based" exchange environment of Linked Data by discussing challenges faced during the conversion. These challenges include silos like the Library's media asset management system Merged Audio-Visual Information System (MAVIS), aligning PBCore with the bibliographic Linked Data model BIBFRAME, modelling differences in works between archival moving image cataloguing and other domains using Entertainment Identifier Registry IDs (EIDR IDs), and possible alignments with EBUCore (the European Broadcasting Union Linked Data model) to address gaps between PBCore and BIBFRAME.